Great Tits build shallower nests than Blue Tits. (1st December 2014) - Lambrechts, Marcel; Demeyrier, Virginie; Fargevieille, Amélie; Giovannini, Pablo; Lucas, Annick; Marrot, Pascal; Midamegbe, Afiwa; Perret, Philippe; Charmantier, Anne; Doutrelant, Claire; Grégoire, Arnaud
Comparative studies predicted or reported weaker or stronger positive relationships between nest size and body size both within and across avian species. Here we show that in relatively small nest-chambers, larger Great Tits (Parus major) build shallower nests than smaller Blue Tits (Cyanistes caeruleus). Our results from the Mediterranean region support findings from published studies that were conducted at more northerly latitudes (UK and Poland). Potential impacts of the local climate and predation risks on the species-specific expression of the size of fresh nests are discussed.